MANAJEMEN SARANA DAN PRASARANA DALAM PROSES MENINGKATKAN KEMAMPUAN BELAJAR ANAK USIA DINI - Adinda Wulandari; Retno Wulandari (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2023)
The purpose of this study was to determine the management or management of facilities and infrastructure in the process of improving early childhood learning abilities. Where in the teaching and learning process certainly requires supporting facilities and infrastructure. The research method used is a qualitative method with a type of research literature by looking for reference sources from relevant journals. The results of this study indicate that the existence of facilities and infrastructure can support a good teaching and learning process so that in learning it can improve the abilities of children during their development. Even though there are several schools that are incomplete, they can be adapted to what is around them so that the teaching and learning process continues to run well and the abilities of children can also increase and develop optimally.